Pengaruh Karakter Entrepreneur, Literasi Digital, dan Lingkungan Sosial terhadap Minat Berwirausaha Siswa Kelas XI SMK Pawyatan Daha 1 Kediri - Ningsih, Rahayu Setya; Wahyudi, Handri Dian (JPEKA: Jurnal Pendidikan Ekonomi, Manajemen dan Keuangan, 2024)
The problem currently being faced is that in 2022, Vocational High Schools will only succeed in reaching 10.38% in facing the development of the business world. This shows that human resources currently need to focus more on the orientation of producing quality workers, and this needs to be balanced with efforts to create quality entrepreneurs. This study aims to determine the effect of entrepreneurial character, digital literacy and social environment on the interest in entrepreneurship in class XI students of SMK Pawyatan Daha 1 Kediri. This research uses quantitative research with descriptive type. The research population was used by class XI students of Pawyatan Daha 1 Vocational School, Kediri with a sample calculation using the slovin formula to get 176 students. Proportional random sampling was used during the sampling process. The analysis technique used is multiple linear regression analysis. The results of the study show that the entrepreneurial character, digital literacy and environmental variables have a positive and significant effect on the interest in entrepreneurship. With a total effect of adjusted r square of 0.529%. This problem is influenced by how well students understand the knowledge and application of entrepreneurship that has been covered in creative products and entrepreneurship subjects.